38 Evaluation of Sorghum Phenolic Compounds for Their Antimicrobial Activities Against Liver Abscess Causing Pathogens in Feedlot Cattle. (7th May 2021) - Salih, Harith M; Amachawadi, Raghavendra G; Roubicek, Cierra; Sexton-Bowser, Sarah; Wang, Jinrong; Li, Yonghui; Nagaraja, T G
Abstract: Liver abscesses occur in finishing cattle fed high-grain, low-roughage diets. Cattle with abscessed livers seldom show any clinical signs and are detected only at the time of slaughter. Liver abscesses are of significant economic concern to the feedlot industry. Liver abscesses comprise, on average, 67% of all liver abnormalities in cattle slaughtered in the United States with a prevalence of 10–20% and may reduce the value of the beef carcass up to 38 per animal with the most severe abscesses. There are four causative agents of the disease including the two subspecies of Fusobacterium necrophorum, ssp. necrophorum and ssp. funduliforme, Trueperella pyogenes, and Salmonella enterica. Tylosin, supplemented in the feed, is the most commonly used antibiotic in the feedlot industry to prevent liver abscesses. Because of the concerns about antimicrobial resistance, there is a need to find an effective alternative to this antibiotic, and sorghum grain extracts, which are high in phenolic compounds, may have the potential to be used as natural antibiotic alternatives. Our objectives were to investigate the efficacy of phenolic extracts from black, sumac, brown, and burgundy sorghums on liver abscess pathogens. The sorghum phenolics were extracted using 75% aqueous acetone and total phenolic content was determined by spectrophotometrically. Bacterial strains were cultured in Mueller-Hinton broth (Salmonella and Trueperella pyogenes) or anaerobic brain-heart infusion broth (Fusobacterium) with and without sorghum extracts (1 mg/ml) at 12, 24, and 48 hours and bacterial concentrations were determined. If the compound was inhibitory, a micro-broth dilution method was used to quantify the inhibitory activity. Both black and sumac sorghum phenolics inhibited growth of all four bacterial species. Further studies are ongoing to investigate different concentrations and phenolic compounds from varieties of sorghum grains on the liver abscess pathogens.